2009
DOI: 10.1099/mic.0.029496-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a second β-glucoside phosphoenolpyruvate : carbohydrate phosphotransferase system in Corynebacterium glutamicum R

Abstract: The phosphoenolpyruvate : carbohydrate phosphotransferase system (PTS) catalyses carbohydrate transport by coupling it to phosphorylation. Previously, we reported a Corynebacterium glutamicum R b-glucoside PTS encoded by bglF. Here we report that C. glutamicum R contains an additional b-glucoside PTS gene, bglF2, organized in a cluster with a putative phospho-b-glucosidase gene, bglA2, and a putative antiterminator, bglG2. While single gene disruption strains of either bglF or bglF2 were able to utilize salici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…In the C. glutamicum ATCC 13032 strain, disruption of ptsG alone resulted in the marked decrease of glucose consumption (28,29), in contrast to the high glucose utilization ability remaining in the C. glutamicum R ptsG-deficient strain. This is explained by the presence of disrupted bgl PTS genes found in the C. glu- tamicum ATCC 13032 genome (41). The residual glucose transport observed in the ptsG-deficient strain derived from C. glutamicum ATCC 13032 and the ptsG bglF bglF2 triple deletion strain from C. glutamicum R may indicate the presence of another minor glucose transporter.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In the C. glutamicum ATCC 13032 strain, disruption of ptsG alone resulted in the marked decrease of glucose consumption (28,29), in contrast to the high glucose utilization ability remaining in the C. glutamicum R ptsG-deficient strain. This is explained by the presence of disrupted bgl PTS genes found in the C. glu- tamicum ATCC 13032 genome (41). The residual glucose transport observed in the ptsG-deficient strain derived from C. glutamicum ATCC 13032 and the ptsG bglF bglF2 triple deletion strain from C. glutamicum R may indicate the presence of another minor glucose transporter.…”
Section: Discussionmentioning
confidence: 98%
“…Glucose exerts repression mainly at the antitermination step of expression of the bglF gene cluster. Whether glucose affects expression of the bglF gene cluster at transcription antitermination was investigated by using the bglF promoter-lacZ reporter system (41). The bglF promoter-lacZ (bglF-lacZ) and bglF2 promoter-lacZ (bglF2-lacZ) fusions were integrated into the chromosome of wild-type C. glutamicum.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed the presence of posttranscriptional regulation mediated by mRNA binding protein in this industrially important microorganism, and these examples should be expanded in the near future (27,28).…”
Section: Discussionmentioning
confidence: 99%